Digital marketing strategies and consumer purchase decision in e-commerce: The roles of trust and behavioral intention - Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim; Rosely, Nurhidayah; Abdul Wahab, Mohd Hafeez Al-Amin; Muhamad, Mira Qerul Barriah; Ahmad, Nur Azreen Farihah (Journal of Islamic, Social, Economics and Development, 2026)
The rapid growth of e-commerce has transformed the way businesses engage with consumers through digital marketing strategies such as mobile marketing and online advertising. Despite the increasing adoption of these strategies, their effectiveness in influencing actual consumer purchase decisions remains inconsistent, particularly in emerging digital markets where concerns regarding trust and transaction security continue to exist. This study examines the influence of digital marketing strategies on consumer purchase decision through the mediating roles of trust and behavioural intention among Malaysian e-commerce consumers. Guided by the Stimulus–Organism–Response (S–O–R) theory, the study proposes that digital marketing strategies function as external stimuli that shape consumers’ internal psychological evaluations before influencing purchasing behaviour. A quantitative cross-sectional research design was employed, and data were collected from 210 Malaysian consumers with prior online purchasing experience using a structured online questionnaire. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) through SmartPLS 4.0. The findings reveal that digital marketing strategies significantly influence trust and behavioural intention, while trust also positively affects behavioural intention. Behavioural intention was found to have the strongest direct effect on consumer purchase decision. In addition, mediation analysis confirmed that trust and behavioural intention significantly mediate the relationship between digital marketing strategies and purchase decision. The study contributes to the digital marketing and e-commerce literature by providing an integrated explanation of how digital marketing strategies translate into actual purchasing behaviour through sequential psychological mechanisms. The findings also offer practical implications for e-commerce firms and digital marketers in developing trust-oriented and consumer-centred digital marketing strategies to improve online purchase conversion in emerging digital markets.